1988
DOI: 10.1071/wr9880695
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Selection by the Swamp Wallaby, Wallabia-Bicolor, the Red-Necked Wallaby, Macropus-Rufogriseus, and the Common Wombat, Vombatus-Ursinus, in Logged, Burnt Forest Near Bega, New-South-Wales

Abstract: This study examined the habitat selected by the swamp wallaby, Wallabia bicolor, the red-necked wallaby, Macropus rufogriseus, and the common wombat, Vombatus ursinus. The habitats were unlogged forest and three age classes of logged forest at 16 weeks and 72 weeks after a fire in November 1980 in Mumbulla State Forest on the south coast ofNew South Wales. Habitat selection was determined from decay-corrected dung counts. The dung count for each species varied with the topography and age class of the forest, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 4 publications
2
40
1
Order By: Relevance
“…The effects of logging on medium-sized mammals are little known although changes in the distribution and numbers of wallabies has been found (Lunney and O'Connell 1988). The most severe effect of logging is on arboreal mammals, many of which are absent from early stages of regeneration and may be excluded for many years due to the absence of tree hollows (Loyn 1980(Loyn , 1985Recher et al 1987;Smith and Lindenmayer 1988;Lunney 1987).…”
Section: Researchmentioning
confidence: 99%
“…The effects of logging on medium-sized mammals are little known although changes in the distribution and numbers of wallabies has been found (Lunney and O'Connell 1988). The most severe effect of logging is on arboreal mammals, many of which are absent from early stages of regeneration and may be excluded for many years due to the absence of tree hollows (Loyn 1980(Loyn , 1985Recher et al 1987;Smith and Lindenmayer 1988;Lunney 1987).…”
Section: Researchmentioning
confidence: 99%
“…In native Eucalypt forest, swamp wallabies used recently harvested (1-5 year old) areas more than older regenerating and unharvested sites (Di Stefano et al, 2007;Di Stefano et al, 2009;Lunney and O'Connell, 1988), although factors such as topographical position (Lunney and O'Connell, 1988), sex and diel period (Di Stefano et al, 2009) were important factors influencing habitat use at finer spatial and temporal scales. In a plantation forestry environment, Floyd (1980) found that swamp wallaby density was uniformly high at two year old sites and uniformly low at one year old sites.…”
Section: Introductionmentioning
confidence: 99%
“…Eastern grey kangaroos are predominantly grazers (Taylor, 1983), preferring heterogeneous habitats that provide relatively open, high quality foraging sites close to or interspersed with shelter vegetation (Hill, 1981;Moore et al, 2002;Southwell, 1987;Taylor, 1980). In contrast, swamp wallabies are mixed feeders (Davis et al, 2008;Di Stefano and Newell, 2008;Hollis et al, 1986) who prefer densely vegetated habitat, particularly during the day (Di Stefano et al, 2009;Lunney and O'Connell, 1988;Swan et al, 2008;Troy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat requirements for wombats in remnant riparian forests that extend through agricultural landscapes have been rarely quantified, nor have models been developed. However, several ecological studies undertaken throughout the distributional range of wombats (Buchan and Goldney, 1998;Catling and Burt, 1995;Lunney and O'Connell, 1988;McIlroy, 1973;Murray, 2001;Taylor, 1993) provide important evidence as to which ecological factors might predict habitat quality for the species.…”
Section: Introductionmentioning
confidence: 99%
“…Wombats are typically associated with eucalypt forests (Catling and Burt, 1995;Lunney and O'Connell, 1988;McIlroy, 1973). In the narrow riparian forests that extend through agricultural land, however, lower canopy cover may be an important determinant of abundance, as it also appears to be for burrow site selection (Borchard et al,. In Press).…”
Section: Introductionmentioning
confidence: 99%